2018
DOI: 10.1186/s12936-018-2262-0
|View full text |Cite
|
Sign up to set email alerts
|

Micro-epidemiology of malaria in an elimination setting in Central Vietnam

Abstract: BackgroundIn Vietnam, malaria persists in remote forested regions where infections are spatially heterogeneous, mostly asymptomatic and with low parasite density. Previous studies in Vietnam have investigated broad behavioural concepts such as ‘engaging in forest activities’ as risk factors for malaria infection, which may not explain heterogeneity in malaria risk, especially in malaria elimination settings.MethodsA mixed methods study combining ethnographic research and a cross-sectional survey was embedded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 52 publications
0
25
1
3
Order By: Relevance
“…comm. M. Bannister-Tyrell, qualitative study [ 47 ]). In addition, many children from Xe Xua cluster reported sleeping at the school in Tu Nak prior to S6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…comm. M. Bannister-Tyrell, qualitative study [ 47 ]). In addition, many children from Xe Xua cluster reported sleeping at the school in Tu Nak prior to S6.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the current study, previous studies in Ninh Thuan and Binh Thuan Provinces in Central Vietnam, where parasite rates and clinical disease was higher than in the current study, showed that regular forest activity was one of the main risk factors for clinical disease, asymptomatic infection and/or seropositivity [ 5 , 6 , 8 ]. Additional risk factors not captured by the present analysis may affect exposure and in order to identify these, a qualitative ethnographic study was performed in a proportion of the adult population of Trà Cang [ 47 ]. The qualitative study offers an explanation why forest and field activities per se were not consistently associated with seropositivity and exposure, as transmission in the adult population seems maintained by evening outdoor activities that delay or disrupt sleeping in a permanent structure in which a bed net could be hung such as drinking and TV watching in the villages or evening fishing or logging in the field or forest [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many challenges, including rapidly changing malaria transmission patterns and growing resistance to existing anti-malarial drugs. As the case load in Vietnam has fallen, it has become increasingly more difficult to detect and respond to foci [14]. This is especially true where infections are asymptomatic or below the limit of detection by routine microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Targeted investigations aimed at characterizing local conditions for malaria transmission have played an important role in malaria control. 10,11 The joint epidemiological/entomological approach described here allows for systematic characterization of the myriad factors that influence malaria epidemiology in an area, from the Anopheles larvae, the interaction of the adults with the human host, the level of carriage in the human population, the population's access and use of mosquito prevention measures, to the management and recording and…”
Section: Discussionmentioning
confidence: 99%